PENGABDIAN MASYARAKAT: PEMERIKSAAN KESEHATAN DAN PENYULUHAN KESEHATAN BAGI LANSIA DI DESA KARYA UTAMA, PANDEGLANG - Nugroho, Hadi; Sitanggang, Tantri Wenny; Susilawati, Susi; Novriyanti P, Happy; Himmy Azz, Istajib Kulla; Rahman, Anita; Malik, Della Karlina; Aini, Zulfa Nurfhadila; Putri, Ragillia Maharani; Putra, Indra; et al. (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Karya Utama Village in Pandeglang faces challenges in providing integrated health services for the elderly, such as Posbindu. These limitations result in a lack of access to regular health check-ups, increasing the risk of degenerative diseases such as hypertension, diabetes, and mobility impairment. This activity aims to increase elderly awareness of the importance of health checks and exercise as promotive and preventive measures to improve their quality of life. The method used includes preparation, implementation, and evaluation stages. In the implementation stage, health checks include checking blood pressure, blood sugar, cholesterol, and uric acid, followed by health counseling with the theme “The Importance of Exercise at Twilight.” Evaluation was carried out through question and answer to measure the elderly’s understanding of the material. The results showed high enthusiasm from senior citizens and community leaders for this activity. The elderly realized the importance of exercise to improve physical strength, balance, and mental health, and to reduce the risk of degenerative diseases. This intervention proves the effectiveness of a community-based approach in increasing elderly health awareness. This activity is expected to become a model of community empowerment to support the health of vulnerable groups in other areas.